(untitled) (Palíndromo, 2017)
In this paper I propose the analysis of a thesis on Marcel Broodthaers and the invention of its Museum of Modern Art, Department of Eagles, written by Keila Kern, making relations with my dissertation proposal, which I intend to address the playing practices, the invention of rules and their possibilities of transgression.